PENERAPAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KANTOR CAMAT TELUK PANDAN KABUPATEN KUTAI TIMUR - Abu Sammang; Aji Ratna Kusuma (Jurnal Paradigma (JP), 2017)
The purpose of research is to describe and analyze Implementation the District Integrated Administrative Service Standards (PATEN) in Head Office Teluk Pandan East Kutai. Source data extracted from key informants and informant and supported by secondary data. Analysis of the data used is Interactive models developed Milles, Huberman and Saldana. The results showed that the integrated policy administration services districts, which is regulated by Regulation Timar Kutai Regent No. 100 /k.632/2013, which implemented Cantor Head Teluk Pandan is implementable less than optimal or less according to the standard specified. Nonetheless the actions taken by the government districts indication pretty good, and it can be known parameters or service standards are set not meet expectations even then the applicative service that the organizing institutions, including quite effective, and is indicated by the ease of access that is done through a pattern of integrated services, so that people no longer confronted by a high sacrifice. Less than optimal implementation of integrated administrative services caused by lock of competent personnel, facilities and infrastructure quality and the small operating budget.Keywords: implementation, integrated administrative service